Vegetable choline as a replacement for choline chloride in broiler feed - Petrolli, Tiago Goulart; Petrolli, Rafaella Rossetto; Aniecevski, Edemar; Facchi, Caroline Schmidt; Leite, Felipe; Dal Santo, Alícia; Pagnussatt, Heloísa; Calderano, Arele Arlindo (Acta Scientiarum. Animal Sciences, 2021)
The objective of this study was to determine choline chloride replacement effects by a vegetable choline source, compost by Trachyspermum amni, Citrullus colocynthis, Achyranthus aspera, and Azadirachta indica in broiler feed. These compounds are fonts of phosphatidylcholine, a high-disponible molecule for intestinal absorption and choline supply. A total of 640 animals were randomly allocated in a completely randomized design, with four treatments and eight repetitions (n = 20), and zootechnical performance (body weight, weight gain, feed conversion ratio, and productive efficiency index), carcass yield, cuts yield, and organs (heart, liver, proventriculus, gizzard, and small intestine) relative weights were evaluated. Were evaluated two choline chloride levels (600 and 800 mg kg-1) and two vegetable choline levels (100 and 200 mg kg-1), added in a corn-soybean meal basal diet, during 42 days of raising. Results revealed better feed conversion ratio (p < 0.001) and production efficiency index (p < 0.001) in broilers fed vegetable choline, with no differences on body weight (p = 0.372) and weight gain (p = 0.427) among broilers. Carcass, cuts yield, and organ relative weights do not alter (p > 0.05) due to different group of supplementations. Findings in this trial concludes vegetable choline can adequately replace choline chloride in broiler feed, with improvement on performance and no compromising carcass, cuts or organ development.